O processo de reconstituição da confiança na governança corporativa: estudo de caso em uma empresa familiar - Rocha, Denise Casagrande da (Universidade do Vale do Rio dos Sinos, 2019)
The scandals involving Brazilian corporations (whether family companies or not) and their respective corporate governance arise the need for debate on the subject of restoring trust and reliance. However, situations such as severe financial difficulties (judicial reorganization, bankruptcy, etc.), lack of alignment between shareholders and managers, disputes or corporate ruptures and the radical discontinuity in succession (due to death, failure to prepare successors, etc.) can also impact the organizational trust and reliance significantly.Besides, based on a literature review on trust and reliance in family companies in the leading Journals of Administration, it could be verified that the topic of trust and reliance in family companies is treated as adjacent, and that issues related to bankruptcy and the rebuilding of trust are little explored, let alone in the context of family businesses.Therefore, considering the importance of this topic, this thesis aims at trying to answer to the following question: How does the process of reconstituting trust and reliance work in corporate governance in family companies? An exploratory qualitative approach was used, having as a research method the single case study analysis, with emphasis on "process analysis".The case studied refers to a Brazilian family business, which is very successful in its field (industry), having been founded 50 years ago and currently under the control of the 2nd Generation. The founders were always recognized by the public for their integrity with businesses and also for their dedication to the work and competence with which they managed the Company.The Company had the confidence of its stakeholders shaken due to the unexpected death of the founding couple, the lack of internal evolution of the corporate governance process and the lack of preparation of their heirs (two children) to assume the management of the Company immediately. The research offers an empirical, theoretical contribution on how the process of reconstitution of organizational trust and reliance dynamically occurs and from the analysis of the area (family business studied). In view of this, the in-depth process was examined, identifying the phases developed, the critical events that marked each of the phases, the sequence of actions performed and the categories that emerged (1st, 2nd and 3rd Orders) during the time (from the breakdown of confidence to the completion of the research). Institutional Theory was used mainly to deal with the subject of corporate governance, and the Stakeholder Theory aimed to capture the perspective of the stakeholders concerning the process. Finally, an empirical, theoretical model is presented on the process of reconstituting trust in corporate governance in the Company studied.
Keywords: Reconstituição da Confiança; Governança Corporativa; Empresas Familiares; Reputação Empresarial; Teoria Institucional; Teoria dos Stakeholders; Rebuild of Trust; Corporate Governance; Family Business; Corporate Reputation; Institutional Theory; Stakeholder Theory; ACCNPQ::Ciências Sociais Aplicadas::Administração